PROMOSI PERPUSTAKAAN MELALUI KEGIATAN PERLOMBAAN DI PERPUSTAKAAN UMUM KOTA PAYAKUMBUH - shindy aldratama putri; rika jufriazia manita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Abstract The main problem in this thesis is to find out the procedures for implementing library promotion and what results the library gets after carrying out library promotion through media competitions at the Payakumbuh Public Library. The purpose of this study is to find out the competition activities held by the Payakumbuh City Public Library and how the Payakumbuh City Public Library seeks existing constraints to carry out competition activitie This type of research is descriptive qualitative. Data collection techniques through observation, interviews with librarians, employees and users at the Payakumbuh City Public Library, and documentation. Data analysis techniques start from data reduction, data presentation and drawing conclusions. Guaranteeing the validity of the data in this study uses source triangulation.Based on the results of the research, (1) the Public Library of Payakumbuh City conducts competition activities to support library promotion activities and attract the public to come to the library, routine activities are held every year, namely story telling competitions and poetry reading competitions. (2) after carrying out the competition activities the results obtained by the Payakumbuh City Public Library were that the community knew about the existence of the library so that it increased interest in visiting the community to come to the library, increasing the literacy of the community around the library. (3) the constraints faced by the library, namely in terms of inadequate human resources, funds (budget) that are not in accordance with the expected plan to carry out activities so that the Payakumbuh City Public Library reduces the quota of participants who take part in competitions, and inadequate library facilities so that efforts carried out by the library involving all employees of the Payakumbuh Public Library, as well as in terms of facilities the Payakumbuh Public Library rented tents and stages for performances